Personal Resources of Psychological Safety of Students Studying in New Territories of the Russian Federation - Irina A. Baeva; Elena B. Laktionova; Irina V. Kondakova; Yulia S. Savenko (National Research Mordova State University, 2024)
Introduction. The state of a person's psychological safety determines his/her effective functioning in a crisis situation. The significance of this state and its support increase sharply in a social situation of uncertainty, in which there is no stability of the external environment and there are many threats to the physical and mental status of a person. Such a tense sociocultural situation is currently typical for the new territories of the Russian Federation. The aim of the study is empirical substantiation of the structure of psychological safety of students studying in new territories of the Russian Federation, and the identification of personal resources that support this state. Materials and Methods. The study sample consisted of 1,034 people studying in the Zaporozhye region. Methods for collecting empirical data: a questionnaire of subjective well-being; indices of acceptance of aggressive, addictive, self-harming, suicidal, risky, delinquent behavior as normative and acceptance of the ideas of extremism, nationalism, xenophobia, fascism; "TromsØ Social Intelligence Scale", "Cognitive Regulation of Emotions", "Life Style Index"; indicators reflecting value orientations related to human life, health and safety, value orientations of social interaction and personal development were used. Factor and linear regression analyzes were used to process the data. Results. The structure of psychological safety of students studying in new territories of the Russian Federation has been empirically determined. It consists of 7 components: subjective well-being, assessment of the acceptance of such forms of behavior as aggressive, addictive, self-harming and suicidal, risky, delinquent as normative, as well as assessment of acceptance of ideas of extremism, nationalism, xenophobia and fascism. The composition of personal resources of the state of students' psychological safety in a tense sociocultural environment has been proven. Discussion and Conclusion. The identified personal resources of psychological safety of students studying in new territories of the Russian Federation are the basis for developing a model of psychological and pedagogical support in an educational organization and creating psychological technologies that meet the real needs of a tense socio-cultural environment.